The Effectiveness of Gargling with Salam Leaf Boiled Water Reducing Plaque Score - Listrianah; Fitri Pratiwi; Ismalayani; Abu Hamid (International Journal Scientific and Professional (IJ-ChiProf), 2022)
Background: Health is the most important part in human life. Plaque is a soft deposit, which is firmly attached to the surface of the teeth. Bay leaves (Syzygium polyanthum) which contain active compounds such as tannins, flavonoids and essential oils that can inhibit bacterial growth. Title: The Effectiveness of Gargling with Bay Leaf Decoction on Decreasing Plaque Score in Adults in Sukabangun 1 RT 19 Sukarami District. Objective: To determine the effectiveness of gargling boiled water with bay leaves on reducing plaque scores. Methods: this study uses a quasi- experimental research method (quasi-experimental). Respondents: adults in Sukabangun 1 RT 19, Sukarami District. Results: The results of the One Way Annova statistical test on plaque index examination before gargling with boiled water, 1 hour after, and 2 hours after with good, moderate, and bad criteria, obtained a P-value of 0.010 which means significant, meaning for gargling water Salam leaf decoction with PHP can reduce plaque scores. Conclusions: 1. The average plaque index before gargling with bay leaf boiled water was 3.09 (Medium) 2. The average decrease in plaque index after gargling was 2.45 (Medium) 3. The effectiveness of bay leaf decoction is able to reduce plaque scores in the treatment before rinsing and after rinsing, this is evidenced by the decrease in plaque scores and the One Way Annova statistical test.